Circulating microRNA-27a and -133a are negatively associated with incident hypertension: a five-year longitudinal population-based study. (23rd June 2022) - Suzuki, Koji; Yamada, Hiroya; Fujii, Ryosuke; Munetsuna, Eiji; Yamazaki, Mirai; Ando, Yoshitaka; Ohashi, Koji; Ishikawa, Hiroaki; Mizuno, Genki; Tsuboi, Yohiski; Hashimoto, Shuji; Hamajima, Nobuyuki
Abstract: Background: Previous cross-sectional studies have shown that several circulating microRNA levels are associated with hypertension, but there are no prospective studies among general populations. Objective: We evaluated the impact of circulating inflammatory- and oxidative stress-responsive microRNAs on changes in blood pressure and the development of hypertension in normotensive Japanese. Method: The study subjects were 84 normotensive participants (33 men and 51 women) who were given a health examination in both 2012 and 2017. In five years, 29 participants developed hypertension. Serum levels of miRNAs (miR-21, miR-27a, and miR-133a) were measured using qRT-PCR. Odds ratios (ORs) and 95% confidence intervals (CIs) for incident hypertension were estimated by logistic regression analysis. Results: Serum miR-27a and -133a levels were lower in newly hypertensive subjects compared with normotensive subjects. With 1-unit lower serum miR-27a and -133a, the confounders adjusted ORs and 95% CI for incident hypertension were 0.84 (0.72–0.96) and 0.75 (0.58–0.91), respectively. The group with high levels of serum miR-27a and -133a had lower ORs than the group with low levels of these miRNAs (OR and 95% CI of miR-27a: 0.29, 0.08–0.91; miR-133a: 0.08, 0.01–0.37, respectively). Conclusions: Circulating miR-27a and -133a are potential biomarkers for the prediction and prevention of hypertension.